Target therapy in metastatic pheochromocytoma: current perspectives and controversies - Amrallah A. Mohammed; Ayman M. El-Shentenawy; Mohamed A. Sherisher; Hani M. El-Khatib (Oncology Reviews, 2014)
Most of the pheochromocytomas (PCCs) are benign neoplasms, but when they are malignant, they can be difficult to treat. Despite advances in diagnosis and imaging, it remains an untreatable tumor, when metastases develop. A deeper understanding of the alteration of the specific molecular pathways causing malignant PCCs might hopefully lead in the future to the development of multiple molecular-targeted therapies to treat it successfully. Clinical experience and the use of murine models of metastatic PCCs have helped introduce new experimental treatment options which will significantly help the PCCs community explore novel targeted therapies that have already shown promising results in many other types of tumors.